Market of Mechanism and Fair Pricing in Islamic: Nejatullah Siddiqi Persfective A Study of Modern Economic Phenomena - Basri Basri (Jurnal Ilmiah Ekonomi Islam, 2023)
The discourse on market mechanisms and pricing in Islam emphasizes that they need to be regulated in order to create balance and justice in the economic sector. Contemporary Islamic economic thinker Nejatullah Siddiqi also provides color when reconstructing economic issues. This article aims to discuss the thoughts of economic figure Nejatullah Siddiqi relating to market mechanisms and fair pricing in Islam. This research uses library research with a descriptive approach as a tool to analyze economic phenomena that have relevance to the context of market mechanisms and pricing. The market mechanisms offered by Nejatullah to run well, such as economic settlement with Asasi, consumers behavior in accordance with Islamic guidelines, and government intervention, The analysis of modern economic phenomena reveals several realities, such as monopolies, dumping, and cartel business. In addition, pricing reveals problems such as information asymmetry and predatory pricing.